(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Wireless power transfer (WPT) has the potential to revolutionise global transportation and to catalyse the rise of the market for electric vehicles (EVs) by providing a compelling alternative to the conventional ways of charging that involve the use of cables. Nevertheless, coil misalignment, which is caused by the behaviours of drivers who park their vehicles, is a substantial challenge since it has a detrimental impact on power transfer efficiency (PTE). This work presents a unique coil design that is coupled with adaptive hardware in order to improve power transfer efficiency (PTE) in magnetic resonant coupling waste power transfer (WPT) systems and reduce the impacts of coil misalignment, which is a significant impediment that is preventing the broad implementation of WPT for electric vehicles (EVs). Simulation with ADS was used to validate the effectiveness of the new design, which exhibited a high degree of congruence with the theoretical analysis. In addition, receiver and transmitter circuitry that was specifically constructed for the purpose of simulating real-world vehicle and parking bay settings was utilised. This allowed for the collecting of PTE data in a controlled environment that was on a smaller scale. Experiments showed that there was a significant thirty percent improvement in the power transfer efficiency (PTE) at the centre of the coil array, and an astonishing ninety percent improvement was recorded when the array was misaligned by three quarters of its radius. When compared to single coil designs that serve as benchmarks, the suggested new coil array displays improved property transfer efficiency (PTE).